2010
DOI: 10.1002/cncr.25068
|View full text |Cite
|
Sign up to set email alerts
|

A prospective cohort study defining utilities using time trade‐offs and the Euroqol‐5D to assess the impact of cancer‐related lymphedema

Abstract: BACKGROUND The devastating impact of lymphedema on cancer survivors’ quality of life has prompted consideration of several changes in medical and surgical care. Unfortunately, our understanding of the benefits gained from these approaches relative to their cost remains limited. This study was designed to estimate utilities for lymphedema and characterize how utilities differ between subgroups defined by lymphedema etiology and distribution. METHODS A consecutive sample of 236 subjects with lymphedema seen at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 35 publications
1
42
0
1
Order By: Relevance
“…Stage I lymphedema was excluded because it is easily overlooked by physicians. Given that lymphedema obviously exacerbates the patients' quality of life even in stage I [2], and because immediate intervention is particularly important in preventing lymphedema progression, it may be worthwhile to include stage I cases in a reevaluation of the risk factors for LLL while incorporating methods to quantitatively evaluate mild lymphedema, such as volume measurement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stage I lymphedema was excluded because it is easily overlooked by physicians. Given that lymphedema obviously exacerbates the patients' quality of life even in stage I [2], and because immediate intervention is particularly important in preventing lymphedema progression, it may be worthwhile to include stage I cases in a reevaluation of the risk factors for LLL while incorporating methods to quantitatively evaluate mild lymphedema, such as volume measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its chronic and incurable nature, lymphedema causes problems for gynecological cancer survivors in the form of functional and aesthetic defects as well as psychological sequelae, thereby reducing their quality of life [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic lymphedema that arises as a consequence of impaired lymphatic drainage causes symptomatic, functional and aesthetic defects as well as psychological sequelae, thereby reducing the quality of life for gynecological cancer survivors [1][2][3]. The reported frequency of lower limb lymphedema secondary to treatment of gynecological cancers ranges from 10% to 49% [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Reaching into rural areas with a wider socioeconomic range would be beneficial. Other studies have reported that women with lower income and cormbidities have experienced higher inidence of lymphedema (Cheville, Almoza, Courmier, & Basford, 2010;S. H. Ridner & Dietrich, 2008).…”
Section: Discussionmentioning
confidence: 91%